2021
DOI: 10.3390/w13121642
|View full text |Cite|
|
Sign up to set email alerts
|

The Ecological Relationship of Groundwater–Soil–Vegetation in the Oasis–Desert Transition Zone of the Shiyang River Basin

Abstract: Groundwater is an important ecological water source in arid areas. Groundwater depth (GWD) is an important indicator that affects vegetation growth and soil salinization. Clarifying the coupling relationship between vegetation, groundwater, and soil in arid areas is beneficial to the prevention of environmental problems such as desertification and salinization. Existing studies lack research on the water–soil–vegetation relationship in typical areas, especially in shallow groundwater areas. In this study, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…Qi et al [49] identified the ecological thresholds of the groundwater depth and TDS content (groundwater depth: 4.8-6.1 m, TDS: 0.37-1.25 g/ L) in Qian'an County by combining indoor tests with remote sensing technology. Cao et al [50] suggested that the groundwater depth should be maintained at 4-10 m and the TDS at <3 g/L to alleviate salinization and desertification in the Shiyang River Basin. These studies suggest that studying the ecological thresholds of the groundwater depth and TDS can provide scientific support for groundwater management in oasis areas to prevent salinization and desertification.…”
Section: Discussionmentioning
confidence: 99%
“…Qi et al [49] identified the ecological thresholds of the groundwater depth and TDS content (groundwater depth: 4.8-6.1 m, TDS: 0.37-1.25 g/ L) in Qian'an County by combining indoor tests with remote sensing technology. Cao et al [50] suggested that the groundwater depth should be maintained at 4-10 m and the TDS at <3 g/L to alleviate salinization and desertification in the Shiyang River Basin. These studies suggest that studying the ecological thresholds of the groundwater depth and TDS can provide scientific support for groundwater management in oasis areas to prevent salinization and desertification.…”
Section: Discussionmentioning
confidence: 99%
“…; a value of 0 tends to represent rock or bare soil; a positive value represents different degrees of vegetation coverage, and the larger the value, the higher the vegetation coverage. Remote sensing data were collected from Landsat satellite data during 2000-2017, with a temporal resolution of 16 days and a spatial resolution of 30 m. Based on the annual mean value of NDVI calculated by 30 m spatial resolution Landsat satellite data [56] and long-term observation data of groundwater depth in the Minqin Basin that were collected from 2000 to 2017, the relationship curve between groundwater depth and NDVI value was established to determine the index of GEF degeneration classification and early warning in the natural vegetation oasis area. Qingtu Lake wetland is a seasonal water area, which needs artificial water conveyance to maintain a certain water area after agricultural irrigation in August every year.…”
Section: The Ndvimentioning
confidence: 99%
“…Groundwater is not only an essential guarantee of water for human production and life (Huang et al, 2022; Shi et al, 2021) but also has an irreplaceable role in the oasis (Lozano et al, 2013). In the arid zone of northwest China, vegetation in artificial and natural oases is strongly dependent on groundwater (Gries et al, 2003; Martinetti et al, 2021; Tamea et al, 2009), providing vegetation water demand (Wang, Wang, et al, 2018; Wang, Yu, et al, 2018), regulating soil water content (Cao et al, 2021), salinity (Wang et al, 2013), and balancing water use in abundant and dry years (Gao et al, 2020; Wada et al, 2012; Wang et al, 2023). However, climate change (Devkota & Gyawali, 2015; Shrestha et al, 2017; Tan et al, 2017) enhanced the impacts of human activities (Riley et al, 2019; Scanlon et al, 2005), turning groundwater evolution more complex.…”
Section: Introductionmentioning
confidence: 99%